Effect of exercise and nutritional supplementation on health-related quality of life and mood in older adults: the VIVE2 randomized controlled trial - Åsa von Berens; Roger A. Fielding; Thomas Gustafsson; Dylan Kirn; Jonathan Laussen; Margaretha Nydahl; Kieran Reid; Thomas G. Travison; Hao Zhu; Tommy Cederholm; Afsaneh Koochek (BMC Geriatrics, 2018)
Abstract Background Health-related quality of life (HRQoL) and absence of depressive symptoms are of great importance for older people, which may be achieved through lifestyle interventions, e.g., exercise and nutrition interventions. The aim of this investigation was to analyze the effects of a physical activity program in combination with protein supplementation on HRQoL and depressive symptoms in community-dwelling, mobility-limited older adults. Methods In the Vitality, Independence, and Vigor 2 Study (VIVE2), community-dwelling men and women with an average age of 77.5 ± 5.4 years, some mobility limitations and low serum vitamin D levels (25(OH)Vit D 22.5–60 nmol/l) from two study sites (Stockholm, Sweden and Boston, USA) were randomized to receive a nutritional supplement or a placebo for 6 months. All took part in a physical activity program 2–3 times/ week. The primary outcome examined in VIVE2 was 400 M walk capacity. HRQoL was measured using the Medical Outcomes Study 36-item Short Form Health Survey (SF36), consisting of the Physical Component Summary (PCS) and Mental Component Summary (MCS), and depressive symptoms were measured using The Centre for Epidemiologic Studies Depression Scale (CES-D). In the sensitivity analyses, the sample was divided into sub-groups based on body measures and function (body mass index (BMI), appendicular lean mass index (ALMI), handgrip strength and gait speed). Results For the whole sample, there was a significant improvement in both MCS, mean (95% CI) 2.68 (0.5, 4.9) (p 0.02), and CES-D -2.7 (− 4.5, − 0.9) (p 0.003) during the intervention, but no difference was detected between those who received the nutritional supplement and those who received the placebo. The results revealed no significant change in PCS or variation in effects across the sub-categories. Conclusions This study demonstrates that a six-month intervention using a physical activity program had positive effects on mental status. No additional effects from nutritional supplementation were detected. Trial registration Registered at ClinicalTrials.gov, March 2 2012, NCT01542892.